An Organoid for Woven Bone. (9th March 2021) - Akiva, Anat; Melke, Johanna; Ansari, Sana; Liv, Nalan; van der Meijden, Robin; van Erp, Merijn; Zhao, Feihu; Stout, Merula; Nijhuis, Wouter H.; de Heus, Cilia; Muñiz Ortera, Claudia; Fermie, Job; et al.
Abstract: Bone formation (osteogenesis) is a complex process in which cellular differentiation and the generation of a mineralized organic matrix are synchronized to produce a hybrid hierarchical architecture. To study the mechanisms of osteogenesis in health and disease, there is a great need for functional model systems that capture in parallel, both cellular and matrix formation processes. Stem cell‐based organoids are promising as functional, self‐organizing 3D in vitro models for studying the physiology and pathology of various tissues. However, for human bone, no such functional model system is yet available. This study reports the in vitro differentiation of human bone marrow stromal cells into a functional 3D self‐organizing co‐culture of osteoblasts and osteocytes, creating an organoid for early stage bone (woven bone) formation. It demonstrates the formation of an organoid where osteocytes are embedded within the collagen matrix that is produced by the osteoblasts and mineralized under biological control. Alike in in vivo osteocytes, the embedded osteocytes show network formation and communication via expression of sclerostin. The current system forms the most complete 3D living in vitro model system to investigate osteogenesis, both in physiological and pathological situations, as well as under the influence of external triggers (mechanical stimulation, drug administration). Abstract : Primary human bone marrow stromal cells are used to create a functional organoid for bone formation, where advanced microscopy and spectroscopy show simultaneous cellular differentiation and matrix mineralization under biological control. Such organoids are promising models to study the molecular mechanisms of diseases or drug delivery, which decreases the need for animal experiments while opening routes toward personalized medicine.